The Relationship of Critical Thinking Skills and Misconceptions on Science Learning - Yolviansyah, Fauziah; Siregar, Juita; Maison (Thinking Skills and Creativity Journal, 2022)
One of the abilities needed in learning is critical thinking skills. Critical thinking skills are skills that can analyze and evaluate information. Critical thinking skills can relate to the occurrence of misconceptions. This relationship can be positive or negative for students. The research objective is to analyze the relationship between critical thinking skills and misconceptions using a five-tier instrument. The method used in this research is correlational. The sampling technique used simple random sampling, taking 25% of the population of 80 students. The data collection instrument used a questionnaire on critical thinking skills and a misconception test sheet. The descriptive results of misconceptions are 6.00, meaning that misconceptions are categorized as moderate. The descriptive results of critical thinking skills show that the mean of critical thinking skills is 68.50, meaning that critical thinking skills are considered good. Then from the correlation results, there is a significant relationship between the two variables. It means that there is a relationship between critical thinking skills and misconceptions. When misconceptions are high, students' critical thinking skills will be low. Conversely, if the misconceptions experienced by students are low, the critical thinking skills possessed by students are high.